Analisis Kelayakan Finansial Industri Pengalengan Keumamah di Kawasan Pelabuhan Perikanan Samudera Kutaraja Banda Aceh - Idal Bahri; Yunida Pangastuti; Mohd. Isa T. Ibrahim; Mahyuddin Mahyuddin (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2022)
Wooden fish in Acehnese language called engkot keumamah is raw fish that is boiled and then dried in the sun for 2 days if the sun is bright, if the sun is not bright, the drying can take up to 2 to 4 days. The main raw material for making wooden fish comes from skipjack tuna. Wood fish can be stored for months, even years. To consume wooden fish, first slice it into thin and small pieces (chips) and then add spices, in the form of a mixture of red chilies, small chilies, sunti acid, shallots, garlic and salt to taste. Based on the potential of fisheries and the improvement of the Lampulo PPS infrastructure, the Banda Aceh City Government should carry out a transformation of competitive and sustainable fisheries development. Therefore, it is necessary to innovate the latest (effective) technology. Strengthening and developing the downstream fisheries industry, such as fish processing and canning. One of the efforts that must be made by the Banda Aceh city government is canning ready-to-eat wooden fish. This is very synergistic with what has been done by the community of Lampulo Village in producing wooden fish (eungkot keumamah). The results of the investment feasibility calculation show that the keumamah fish canning business is feasible and even profitable, because at an interest rate (discount factor) of 14% per year, the Net B/C is 2.19 (>1) and the NPV is Rp. 2,821,481,537.14,– (> 0). With an IRR value of 40.46% (> DF 14%), it means: this project is feasible even though the interest rate (discount factor) reaches 40.46% per year.